Meta-analysis identifies novel risk loci and yields systematic insights into the biology of male-pattern baldness - Stefanie Heilmann-Heimbach (Nature Portfolio, 2017)
Male-pattern baldness is a common condition in which hair is progressively lost from the scalp. Here, the authors find 23 new genetic variants associated with this condition and suggest that it is not an isolated trait but may share an underlying biological basis with various diseases.